Metrics and experimental data for assessing unbalanced disassembly lines. (1st January 2011) - McGovern, Seamus M.; Gupta, Surendra M.
Disassembly lines are inherently multicriteria, with balance having the possibility of being one of the lower priorities. In addition, complete disassembly may not be desired, required, or even possible, resulting in only partial disassembly being conducted. The result may be a disassembly sequence that readily satisfies the decision-maker's primary requirements, but at the expense of an unbalanced line. However, obtaining the decision-maker's primary requirements may not sufficiently justify exceptionally poor balance. Alternatively, the difference between a balanced disassembly line and one that is unbalanced may be so insignificant that a focus purely on balance may obfuscate the benefits of considering other criteria. Therefore, metrics are needed to evaluate the merits of all considered criteria, including the level of balance (or unbalance). In this paper, a multicriteria benchmark dataset and associated metrics are developed for use in quantitatively evaluating an unbalanced paced disassembly line.